Crisis management during anaesthesia: pulmonary oedema. Issue 3 (2nd June 2005) - Chapman, M J; Myburgh, J A; Kluger, M T; Runciman, W B
Abstract : Background: Pulmonary oedema may complicate the perioperative period and the aetiology may be different from non-operative patients. Diagnosis may be difficult during anaesthesia and consequently management may be delayed. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for pulmonary oedema, in its management occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: Pulmonary oedema was identified in 35 (<1%) of the first 4000 reports to AIMS. The most frequent presenting sign was hypoxia (46%) and the most specific sign was the presence of frothy sputum (23%). The core algorithm, although successful in the management of the initial physiological upset, was found to be inadequate for the ongoing management of pulmonary oedema. A specific sub-algorithm for the management of perioperative pulmonary oedema was devised, tested against the reports and would have been effective, if properly applied, in the management of all but one of the reported cases. Conclusion: Successful recognition and management of perioperative pulmonary oedema is likely with the application of the structured algorithm and specific sub-algorithm approach outlined in this study.